'There are only monsters': an interview with Emil Ferris. Issue 4 (4th July 2021) - Porter, Whitney
ABSTRACT: Before her keynote address at the Michigan State University Comics Forum in February 2020, Emil Ferris and Whitney Porter met to talk about monsters, comics, and creativity. In addition to sharing more insight into her first, and Eisner award-winning, comic My Favourite Thing is Monsters, Ferris discusses her philosophy on finding and embracing the monster in ourselves. She talks about how a return to the woods, a greater awareness of the earth, might help us to find our monster selves and to share our stories. In this interview Ferris shares what she hopes to find in comics and cautions creators from sending us into the texture-less land of what she jokingly calls, 'Smoothie World.' As a creator and as a storyteller, Ferris is generous, vulnerable, and invitational as she leads with empathy and hopes we do the same through monsters and the 'magic' of comics.